2016
DOI: 10.1007/s10334-016-0557-0
|View full text |Cite
|
Sign up to set email alerts
|

7 Tesla quantitative hip MRI: a comparison between TESS and CPMG for T2 mapping

Abstract: TESS seems to be an attractive alternative to CPMG for improvements in quantitative hip joint imaging at 7 T, allowing shortening of the total acquisition time paired with insensitivity to B1, while rendering comparable image quality with good repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…T2 and T2* mapping of hip cartilage at lower field strengths (1.5 and 3 Tesla) is confounded by the very thin cartilage surfaces on the femoral head and acetabulum, leading to partial volume effects from surrounding tissues. They were able to achieve higher resolution (5 slices at 0.5 mm × 0.5 mm in plane resolution with 2.5 mm thick slices) than previous studies at 3 Tesla in clinically reasonable scan times at 7 Tesla (under 5 minutes for the T2 map, T2* maps in under 2 minutes), and found that the increased resolution gained by going to 7 Tesla was essential to mitigate partial volume contamination (11,12). This had the advantage of lowering SAR (lower tissue heating), and allows higher resolutions and/or increased volume coverage in a true 3D scan.…”
Section: T2 and T2* Mappingmentioning
confidence: 85%
“…T2 and T2* mapping of hip cartilage at lower field strengths (1.5 and 3 Tesla) is confounded by the very thin cartilage surfaces on the femoral head and acetabulum, leading to partial volume effects from surrounding tissues. They were able to achieve higher resolution (5 slices at 0.5 mm × 0.5 mm in plane resolution with 2.5 mm thick slices) than previous studies at 3 Tesla in clinically reasonable scan times at 7 Tesla (under 5 minutes for the T2 map, T2* maps in under 2 minutes), and found that the increased resolution gained by going to 7 Tesla was essential to mitigate partial volume contamination (11,12). This had the advantage of lowering SAR (lower tissue heating), and allows higher resolutions and/or increased volume coverage in a true 3D scan.…”
Section: T2 and T2* Mappingmentioning
confidence: 85%
“…Notably, TESS systematically provided lower cartilage T2 values compared to MESE. The overestimation of T2 values obtained with MESE technique was assumed to be related to the stimulated echo contamination due to imperfect refocusing pulses in MESE acquisitions [ 21 , 22 ]. In Table 2 , a summary of the mean T2 values obtained for the cartilage are displayed, showing the variations between different anatomical districts and different T2 mapping techniques [ 26 ].…”
Section: Cartilagementioning
confidence: 99%
“…Musculoskeletal UHF MRI of the hip joints has only recently become accessible at 7T through development of new RF coil technology and RF shimming techniques . Building on these initial studies, a couple of studies have now used the identical hardware setup to perform quantitative MRI of the hip joint employing T 1 , T 2 , and T2* mapping in healthy volunteers as well as in patients (Fig. ).…”
Section: Musculoskeletalmentioning
confidence: 99%